Prevalence and factors associated with depression among the elderly in rural areas of central India: a mixed method study - Dhumal, Komal S.; Bhelkar, Sandeep M.; Narlawar, Uday W.; Pandey, Snigdha; Barela, Shamvel A. (International Journal Of Community Medicine And Public Health, 2024)
Background: The global demographic shift towards an aging population has raised concerns about the mental health of the elderly, particularly in rural areas. This study sought to tackle this issue by quantitatively evaluating the prevalence of geriatric depression in rural areas of central India and qualitatively investigating the factors that contribute to late-life depression. Methods: This mixed-method study conducted in the rural areas of central India aimed to assess the prevalence of depression among the elderly and explore gender-specific factors contributing to late-life depression. Results: Quantitative data were collected from 308 elderly individuals aged 60 years and above, revealing a high prevalence of depressive symptoms (75.6%). Factors significantly associated with depression included female gender, age over 70 years, lower educational attainment, financial dependency, and comorbidities. Qualitative analysis through focus group discussions highlighted gender-specific perceptions of depression risk factors, emphasizing the need for tailored interventions. Conclusions: The findings underscore the urgent need for targeted mental health interventions addressing socio-economic disparities and gender-specific challenges in rural elderly populations. A nuanced, gender-sensitive approach is crucial for promoting well-being and reducing the burden of depression among the elderly in rural central India.